Pemanfaatan Ekstrak Kulit Ubi Jalar Ungu dalam Deteksi Boraks pada Kerupuk Puli yang dijual di Pasar Ngemplak Tulungagung - Lauren, Angelita Rajinia; Asworo, Riska Yudhistia; Widwiastuti, Hanandayu (Lembaga Publikasi Ilmiah Nusantara, 2025)
Method validation is one of the quality assurance processes that must be carried out on a developed Method Anthocyanins in purple sweet potato peel can be used as a reagent in a test kit for method development to detect borax. Borax is a substance prohibited as a food additive, yet it is still commonly found in food products such as kerupuk puli (a type of Indonesian cracker). Therefore, it is necessary to validate the test kit method using purple sweet potato peel extract to determine the borax content in kerupuk puli sold at Ngemplak Market, Tulungagung. The research method used was experimental, involving organoleptic testing, creation of a color comparator, method validation, and both qualitative and quantitative testing of borax in kerupuk puli. Organoleptic results from 5 samples indicated the possible presence of borax, characterized by a crispy texture and a bitter taste. The color comparator produced showed that purple sweet potato peel extract can detect borax, indicated by different color changes corresponding to each variation in borax concentration. The method validation results met the required criteria, including linearity with an R² of 0.996; Limit of Detection (LoD) of 0.028%; Limit of Quantification (LoQ) of 0.095%; accuracy of 101.04%; and Relative Standard Deviation (RSD) of 1.8%. The kerupuk puli samples tested using this method showed the presence of borax at a concentration of 0.0002%.